PENEGAKAN HUKUM TINDAK PIDANA PEMILU TERHADAP PENGGUNAAN HAK PILIH ORANG LAIN - La Ode Hermanto; Syamsul Bachri; Winner A. Siregar (Universitas Muhammadiyah Malang, 2021)
This study aims to determine the implementation of the Kendari City Bawaslu Supervision of Voter Data on the use of voting rights in the 2019 general election and to analyze the enforcement of general election law against the use of other people's voting rights in the 2019 general election. This research method uses empirical normative legal research. . The results of study show that in carrying out its functions and authorities, the Kendari City Bawaslu has not shown optimal performance in the 2019 General Election, as evidenced by; there are still voters who do not meet the requirements are still being recorded, there are still eligible voters who are not registered in the voter list, lower-level technical implementing officers have not shown good work due to understanding of regulations that can change at any time, the professional level of the organizers' work, and the process supervision is not optimal due to limited supervisory personnel. As a recommendation, the Kendari City Bawaslu needs to improve the quality of election management resources so that they can work professionally, accountably, reliably and accurately and with integrity in the next election process.